Analysis of Dynamics Characteristic of the Helical Gear Transmission in Helicopter - Liu Tao; Li Jie; Dai Jinchun (Jixie chuandong)
The multiaxial helical gear transmission is widely used in helicopter for parallel operation. The dynamics model of the helical gear transmission is established for system inherent characteristic analysis,and the dynamic response is obtained. The influence of asymmetrical loads on helical gear dynamics characteristic is analyzed. The analysis shows that the inherent characteristic of the helical gear has good property because of the structural symmetry. When the input loads are symmetry,the motions of the two input gears are identical and certain modal responses are suppressed. The output gear only has rotational and axial vibrations. When the input loads are asymmetric,those suppressed vibrations will show up again and will be more remarkable as the degree of asymmetry gets greater.